2023
DOI: 10.3389/fphar.2023.1283247
|View full text |Cite
|
Sign up to set email alerts
|

Post-marketing safety surveillance of sacituzumab govitecan: an observational, pharmacovigilance study leveraging FAERS database

Wensheng Liu,
Qiong Du,
Zihan Guo
et al.

Abstract: Background and objective: Sacituzumab govitecan (SG), the first antibody-drug conjugate targeting human trophoblast cell-surface antigen 2 (Trop-2), has been approved by the Food and Drug Administration (FDA) for the treatment of advanced or metastatic breast cancer and urothelial cancer. However, there is currently a dearth of information regarding the safety profiles of SG in a large sample cohort. The objective of the present study is to investigate SG-related adverse events (AEs) in real-world settings lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…Approximately 60% of patients treated with SG experienced diarrhea, with around 10% suffering from severe (grade 3) episodes, likely due to the drug dissociating early from its antibody, leading to off-target off-tumor toxicity 16 , 20 . Liu et al identified an association between SG and an increased risk of blood lymphatic system disorders and hepatobiliary disorders 21 . Additionally, they noted that the median onset time for SG-related AEs was 14 days, with the bulk of these events emerging within the first month of treatment, although some AEs continued to manifest up to six months later.…”
Section: Trop2-targeted Therapiesmentioning
confidence: 99%
“…Approximately 60% of patients treated with SG experienced diarrhea, with around 10% suffering from severe (grade 3) episodes, likely due to the drug dissociating early from its antibody, leading to off-target off-tumor toxicity 16 , 20 . Liu et al identified an association between SG and an increased risk of blood lymphatic system disorders and hepatobiliary disorders 21 . Additionally, they noted that the median onset time for SG-related AEs was 14 days, with the bulk of these events emerging within the first month of treatment, although some AEs continued to manifest up to six months later.…”
Section: Trop2-targeted Therapiesmentioning
confidence: 99%